Metallurgical production in northern Eurasia in the Bronze Age - Grigoriev, Stanislav, (Access archaeology., 2015)
Copper is the first metal to play a large part in human history. This work is devoted to the history of metallurgical production in Northern Eurasia during the Bronze Age, based on experiments carried out by the author and analyses of ancient slag, ore and metal.